Supporting Workers with Musculoskeletal Conditions: A Survey of United Kingdom Occupational Therapists' Communications with Clients and Their Employers. (November 2013) - Coole, Carol; Drummond, Avril; Watson, Paul J; Worthington, Esme; Hammond, Alison
Introduction: Musculoskeletal conditions are a common cause of sickness absence and work disability. Little is known about the work-related advice and support that occupational therapists provide to this client group and their employers. The purpose of this study was to report on current occupational therapy practice in this area in the United Kingdom. Method: A questionnaire survey was conducted, of United Kingdom occupational therapists treating employed clients with musculoskeletal conditions in community or outpatient settings. Questionnaires were posted to 960 hospitals or units, identified through National Health Service websites to reach as many respondents as possible, and the survey was also available online. Findings: 257 respondents reported on their provision of work-related advice and support. Of these, over 30% (n = 82) reported that this involved a moderate amount of their time; 60% (n = 154) had experience of contacting employers and 21% (n = 55) had met with clients' employers in the previous year. Time and resources, concern about legal implications, and having the appropriate skills had an impact on communication between therapists and employers. Conclusion: The findings demonstrate considerable variations in service delivery, interventions, and the contact made with employers. These need urgent attention if the profession is to meet the challenges of the government's agenda for improving health at work.